Pengaruh pemberian media poster kesehatan terhadap minat remaja mengikuti posbindu PTM - Anisa Catur Wijayanti; Enggin Putri Edita (Universitas Ahmad Dahlan, 2023)
Non-communicable diseases (NCD) are still a health problem in Indonesia in recent years. Non-communicable diseases often go undetected because no symptoms are found, so they are difficult to cure or will end in disability or death. There has been an epidemiological transition by shifting morbidity and mortality rates from infectious diseases to non-communicable diseases at a young age. The Indonesian government has created a program to overcome the problem of NCDs with the existence of NCDs Posbindu aimed at people over 15 years old who are still healthy and people with NCDs. There is a need to provide information using poster media regarding NCDs and NCDs Posbindu problems in adolescent understanding to prevent and control NCDs now and in the future. This study aims to determine the effect of giving poster media on teenagers' interest in participating in Posbindu at Ambarawa 1 High School. The results of the analysis showed that there was an influence of poster media on teenagers' involve in participating in NCDs Posbindu (p:0,001). The results showed a decrease in the average interest of adolescents in participating in the NCDs Posbindu by 3.15. This happened because adolescents objected to the implementation of the NCDs Posbindu, which was held one a month. Adolescents need to know that participating in Posbindu is an effort to prevent and control NCDs in the future. The data can be provided through cooperation between schools and community health centers that can involve existing extracurriculars and provide a better understanding of the importance of NCDs prevention and control efforts to adolescents, teachers and parents.